Evaluation of Abutilon indicum as Mild Steel Corrosion Inhibitor in 1 M HCl and 0.5 M H2SO4 by Electrochemical Techniques - Saratha, R.; Meenakshi, R. (Asian Journal of Chemistry, 2012)
The present study reports on performance of acid extracts of Abutilon indicum as mild steel corrosion inhibitor in 1 M HCl and 0.5 M H2SO4 solutions studied by electrochemical techniques. The inhibition efficiency was found to be greater than 95 % in acid media and potentiodynamic polarization study revealed that inhibitor as a mixed type of inhibitor in both HCl and H2SO4 acid media controlling anodic and cathodic reactions. Linear polarization study showed increase in resistance and the electrochemical impedance study showed a decrease in double layer capacitance as the adsorption of inhibitor caused structural changes at electrode-solution interface.